Implementation of direction control algorithms for fixed wings UAV - Abdalla, Mohamed K.; Hassan Abdalla Hashim, Aisha; Attia, Tahani A.; Babikir, Sharief F. (Deanship of Scientific Research, SUST, 2015)
The demand for unmanned aircraft vehicles, UAV, has grown quite significantly in recent years. It is therefore important to implement efficient and accurate computer controlled navigation algorithms on such vehicles to guarantee the successful and reliable delivery of the vehicle to its final destination. This paper describes algorithms that use the Global Positioning system data to navigate from the current position to the destination point. The algorithm continuously adjusts the direction of flight thus ensuring the shortest path to the target. The algorithm has been successfully tested within Khartoum Province.